The Effects of a Chactoid Scorpion Venom and Its Purified Toxins on Rat Blood Pressure and Mast Cells Histamine Release - Ettinger, Keren (MDPI, 2013)
The effect of the venom of the Chactoid family of scorpions on blood pressure was scantly investigated and was addressed in the present study using the venom of the Israeli scorpion, Scorpio maurus palmatus. Blood pressure in rats was monitored via cannulated femoral artery, while venom and toxins were introduced into femoral vein. Venom injection elicited a biphasic effect, expressed first by a fast and transient hypotensive response, which lasted up to 10 min, followed by a hypertensive response, which lasted up to one hour. It was found that these effects resulted from different venom components. Phospholipase A(2) produced the hypotensive effect, while a non-enzymatic neurotoxic polypeptide fraction produced the hypertensive effect. Surprisingly, the main neurotoxic polypeptide to mice had no effect on blood pressure. In vitro experiments indicated that the hypertensive factors caused histamine release from the peritoneal mast cells, but this effect is assumed to be not relevant to their in vivo effect. In spite of the cytotoxic activity of phospholipase A(2), it did not release histamine. These findings suggest that the effects of venom and isolated fractions on blood pressure parameters are mediated by different mechanisms, which deserve further pharmacological investigation.